2023
DOI: 10.3389/fpsyt.2023.1070556
|View full text |Cite
|
Sign up to set email alerts
|

A human stem cell-derived neuronal model of morphine exposure reflects brain dysregulation in opioid use disorder: Transcriptomic and epigenetic characterization of postmortem-derived iPSC neurons

Abstract: IntroductionHuman-derived induced pluripotent stem cell (iPSC) models of brain promise to advance our understanding of neurotoxic consequences of drug use. However, how well these models recapitulate the actual genomic landscape and cell function, as well as the drug-induced alterations, remains to be established. New in vitro models of drug exposure are needed to advance our understanding of how to protect or reverse molecular changes related to substance use disorders.MethodsWe engineered a novel induced plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…DNA damage markers were identified in both the striatum of humans and monkeys, suggesting chronic opioid use associated with OUD leads to augmented DNA modifications ( e.g., double-stranded breaks, chromatin accessibility). Elevated markers for neuroinflammation, the involvement of microglia-dependent signaling in striatum, and alterations in synaptic signaling in OUD are consistent with previous bulk transcriptomics findings from postmortem brains of subjects with OUD 2, 34, 108, 126, 127 .…”
Section: Discussionsupporting
confidence: 89%
“…DNA damage markers were identified in both the striatum of humans and monkeys, suggesting chronic opioid use associated with OUD leads to augmented DNA modifications ( e.g., double-stranded breaks, chromatin accessibility). Elevated markers for neuroinflammation, the involvement of microglia-dependent signaling in striatum, and alterations in synaptic signaling in OUD are consistent with previous bulk transcriptomics findings from postmortem brains of subjects with OUD 2, 34, 108, 126, 127 .…”
Section: Discussionsupporting
confidence: 89%
“…At least partially motivated also by regulatory pressures to reduce animal experimentation by exploring in vitro alternatives, the scope of diseases modeled with PSCs has expanded to include psychedelic-targeted disorders such as post-traumatic stress disorder (PTSD), 76 SUD, 77 and depression 78 ( Table 2 ). Despite the increasing popularity of these studies, which have predominantly emerged in the past decade, clinical trials of compounds identified or repurposed via PSC-based models remain constrained and in their nascent stages.…”
Section: What Do Psc-derived Brain Cells Bring To Psychedelic Studies?mentioning
confidence: 99%
“… 91 In a study assessing the effects of morphine treatment as a proxy for chronic opioid exposure, the expression patterns of neuron-related genes such as egr-1 were found to be similar between PSC-derived neurons and the dorsolateral prefrontal cortex of individuals deceased with opioid use disorder. 77 Also, direct neuronal transdifferentiation has emerged as a means to bypass intermediate embryonic-like pluripotent stages, which may erase or modify disease-associated epigenetic traits.…”
Section: What Do Psc-derived Brain Cells Bring To Psychedelic Studies?mentioning
confidence: 99%
“…Altogether, such rapid developments in the generation of iPSC-derived neuronal models of OUD provoked questions regarding their fidelity to in vivo signatures of the disorder. To address this, Mendez et al (2023) , engineered novel iPSC-derived cortical neurons from skin fibroblasts of individuals who had died of an opioid overdose. Following chronic treatment with morphine, these neurons remarkably showed transcriptional alterations paralleling those observed in the postmortem, ex vivo frontal cortex tissue of individuals with OUD ( Mendez et al, 2023 ).…”
Section: Brain Organoid and Spheroid Models Of Opioid Use Disordermentioning
confidence: 99%
“…To address this, Mendez et al (2023) , engineered novel iPSC-derived cortical neurons from skin fibroblasts of individuals who had died of an opioid overdose. Following chronic treatment with morphine, these neurons remarkably showed transcriptional alterations paralleling those observed in the postmortem, ex vivo frontal cortex tissue of individuals with OUD ( Mendez et al, 2023 ). These included developmental and synaptic genes associated with substance use disorders ( Gallo et al, 2018 ; Seney et al, 2021 ), as well G-protein-coupled receptor (GPCR) pathways, of interest given that opioid receptors are GPCRs themselves.…”
Section: Brain Organoid and Spheroid Models Of Opioid Use Disordermentioning
confidence: 99%